Optimization of treatment and prevention of recurrences of bacterial vaginosis in postmenopausal women - S.O. Ostafiichuk; N.V. Drogomyretska; O.M. Kusa; O.V. Neiko; I.V. Levitsky; N.M. Kinash (Medičnì Perspektivi)
The study aimed to improve the effectiveness of treatment and prevention of recurrences of bacterial vaginosis (BV) in postmenopausal women. 87 women with BV aged 50 to 65 who received a course of antibacterial therapy with control clinical and laboratory recovery were examined. In the future, two groups were selected: the first group (42 women) received probiotics in suppositories (live lactobacillus strains L. aktobacillus plantarum 8P-A3 or L. plantarum 38, or L. fermentum 90T-C4, or L. fermentum 39) vaginally 2 times a day for 10 days. Women of the second group (45 patients) received probiotics vaginally once a day for 20 days and a suppository with estriol 0.5 mg vaginally once a day for 2 weeks, and then 2 times a week for 3 months. Evaluation of effectiveness was carried out after 3 and 6 months. A gynecological examination, determination of the pH reaction of vaginal contents, aminotest, microscopy of vaginal smears, bacteriological cultures on nutrient media for the determination of facultatively anaerobic bacteria, Gardnerella vaginalis, quantitative analysis of vaginal microflora, species composition and frequency of lactobacilli were performed. In the women of the first group, the risk of recurrence of the laboratory criteria of BV increases after 3 months: an increase in the pH of the vaginal contents by 1.2 times (p<0.05), the appearance of a positive aminotest in 38.1% of patients, the presence of Gardnerella vaginalis in 26.2% women with a pathological number of 104-105 CFU/ml, regression of the pool of lactobacilli with worsening of the situation and the appearance of clinical manifestations of the disease after 6 months. In the second group, there was a decrease in cases of recovery of laboratory markers after 3 months and clinical and laboratory criteria of BV after 6 months. The study proves the necessity of determining the laboratory criteria for the diagnosis of BV in dynamics 3 months after the main course of antimicrobial therapy in women without a clinical picture of recurrence. The effectiveness of intravaginal use of probiotics and vaginal estriol at a dose of 0.5 mg for the treatment and prevention of BV recurrences in postmenopausal women with a long course has been shown (4 months).